Gasless versus gas-inflated transaxillary endoscopic thyroidectomy for papillary thyroid carcinoma: a cohort study on surgical outcomes and learning curves - Zhao, Qi; Lv, Bin; Sheng, Lei; Liu, Nan (Frontiers in Endocrinology, 2025)
BackgroundConventional open thyroidectomy (COT) results in visible neck scarring. Transaxillary endoscopic thyroidectomy (TET) comprises gasless (suspension-assisted) and gas-inflated approaches, both of which offer superior scar concealment. This study aimed to compare the efficacy and safety of these two endoscopic techniques for treating papillary thyroid carcinoma (PTC).MethodsA total of 471 patients were stratified into three groups: gasless transaxillary endoscopic thyroidectomy (GTET), gas-inflated transaxillary endoscopic thyroidectomy (GITET), and COT. Comparative analyses included perioperative outcomes, complication rates, cosmetic satisfaction and others. The cumulative sum (CUSUM) curve was applied to evaluate the learning curves of GTET and GITET.ResultsPatients in the TET groups were younger and included a higher proportion of females compared to COT. The COT group demonstrated advantages in operation time, postoperative drainage volume, and the number of retrieved central lymph nodes over TET groups. No significant differences were observed among the three groups in postoperative complication rates or sensory abnormalities. However, the COT group had higher swallowing-discomfort incidence. In terms of cosmetic outcomes, GITET surpassed GTET, with lower postoperative pain scores. The learning curves for both GTET and GITET were biphasic, achieving mastery after 42 and 67 cases respectively. No significant difference was found in the efficacy of central lymph node dissection between the two endoscopic approaches.ConclusionBoth GTET and GITET were reliable and safe surgical approaches, with reduced postoperative swallowing discomfort compared to COT. While GITET offered superior cosmetic outcomes and lower postoperative pain scores than GTET, achieving technical proficiency required more cases.